1980
DOI: 10.1104/pp.66.2.321
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Centrifugation as a Method of Extracting an Extracellular Solution from Peas, and Its Use for the Study of Indoleacetic Acid-induced Growth

Abstract: MATERIALS AND METHODSA technique of centrifuging pea epicotyl sections which extracts watersoluble cell wall polysaccharides with less than 1.5% cytoplasmic contamination as revealed by malate dehydrogenase activity determinations was developed. Tests Reactions occurring in the cell wall are often difficult to study because of the problems in separating the solution that bathes the cell wall from the complex solution within the cell. Any process which ruptures the plasmalemma leads to a mixing of intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 12 publications
3
105
0
Order By: Relevance
“…In the current study, the apoplast solution was collected at 480g, well below the force reported to induce leakage. Analyses of immature internode tissues in other species of Saccharum that accumulate sugars have produced iJa values greater than -0.5 MPa, indicating that the high apoplastic solute concentrations were not due to systemic errors in the centrifugation (4,14), while fully hydrated sugarcane stalk tissue yielded sufficient solution for repeated analyses without the addition of water. Contamination from the phloem during centrifugation would not be expected to constitute a large error, since the phloem has been estimated to comprise less than 0.5% of the volume in mature stalk tissue (9).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the apoplast solution was collected at 480g, well below the force reported to induce leakage. Analyses of immature internode tissues in other species of Saccharum that accumulate sugars have produced iJa values greater than -0.5 MPa, indicating that the high apoplastic solute concentrations were not due to systemic errors in the centrifugation (4,14), while fully hydrated sugarcane stalk tissue yielded sufficient solution for repeated analyses without the addition of water. Contamination from the phloem during centrifugation would not be expected to constitute a large error, since the phloem has been estimated to comprise less than 0.5% of the volume in mature stalk tissue (9).…”
Section: Discussionmentioning
confidence: 99%
“…The basic principle is that the whole of the apoplast is filled with water or buffer, usually by vacuum infiltration, followed by connection of the intercellular washing fluid (IWF) by centrifugation at speeds sufficiently low so as to not significantly disrupt the symplast. This method has been used to look at cell wall enzymes and compounds involved in cell growth (Terry & Bonner, 1980) as well as a means of identifying the appearance of proteins and other compounds as a response to infection by pathogens (Rohringer & Martens, 1987). Earlier Klement (1965) studied IWF from tomato leaves for its potential as a substrate for phytobacterial pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble or weakly bound enzymes have been extracted from the apoplast by vacuum infiltration followed by gentle centrifugation (21,(23)(24)(25). This technique works well with stems which require minimal support during centrifugation, but when used with cereals which have thin and relatively fragile leaves it yields small volumes of solution with low protein content (21).…”
mentioning
confidence: 99%
“…By criteria developed in several laboratories (6,9,11,15,17,18,21,25): (a) enzymes washed from tissues by solutions not damaging the plasmalemma are soluble in the apoplast or weakly bound to the cell wall; (b) soluble cytoplasmic enzymes can be obtained by disrupting cells and pelleting organelles and broken cell walls; (c) ionically bound enzymes may be extracted from washed wall pellets by salt solutions of high ionic strength; and (d) enzyme activity remaining in the salt-washed wall pellet is covalently bound or entrapped into the wall. We have applied these criteria in our attempt to localize activity for four enzymes which may have roles in regulating apoplastic phenolic metabolism in young primary leaves of oats and barley.…”
mentioning
confidence: 99%